2020
DOI: 10.1186/s12888-020-02759-x
|View full text |Cite|
|
Sign up to set email alerts
|

Earthquake-related stressors associated with suicidality, depression, anxiety and post-traumatic stress in adolescents from Muisne after the earthquake 2016 in Ecuador

Abstract: Background: The Ecuadorian earthquake in April 16th was the second strongest and deadliest in 2016 worldwide, with approximately one million people affected. In this paper, we analyzed the psychological impact and the relationship between mental health events and various earthquake-related stressors related to the earthquake, 9 months after the event. Methods: We conducted an analytical cross-sectional study, applying an anonymous survey to 316 adolescents (13-19 years old) from Muisne, Ecuador. Suicidal tende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
5
25
2
5
Order By: Relevance
“…The results of this study showed that chronic disease is related to PTSD symptoms. Some previous studies have reached similar conclusions (Gigantesco et al, 2013;Guo et al, 2014;Liao et al, 2019). A study of Fukushima nuclear accident survivors found that, on the one hand, chronic diseases before accidents are one of the predictors of PTSD symptoms; on the other hand, PTSD increases the risks of chronic diseases such as hypertension, hyperlipidaemia, coronary heart disease, etc.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of this study showed that chronic disease is related to PTSD symptoms. Some previous studies have reached similar conclusions (Gigantesco et al, 2013;Guo et al, 2014;Liao et al, 2019). A study of Fukushima nuclear accident survivors found that, on the one hand, chronic diseases before accidents are one of the predictors of PTSD symptoms; on the other hand, PTSD increases the risks of chronic diseases such as hypertension, hyperlipidaemia, coronary heart disease, etc.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with the results of this study, a negative correlation between financial constraints and PTSD symptoms was also observed among survivors of the L'Aquila earthquake, Ecuador earthquake, Hurricane Katrina and mudslides in southwestern China (Chen et al ., 2007 ; Gigantesco et al ., 2013 ; Chen et al ., 2014 ; Gerstner et al ., 2020 ). A review on poverty and disasters pointed out that the impact of disasters on victims varies with social class; compared with the rich, the poor are more vulnerable to trauma both physically and mentally (Fothergill and Peek, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…[32]. On the other hand, a recently published study suggest that younger populations are at greater risk of developing depression and anxiety after experiencing a shocking and stressing event as reported in 2020 [33].…”
Section: Plos Onementioning
confidence: 99%
“…Bu çalışmada 13-19 yaş grubu ergenler değerlendirilmiştir. Sonucunda travma sonrası stres bozukluğu, depresif bozukluk, anksiyete bozukluğu ve intihar düşüncesinde artış saptanmıştır 20 . 976 yılında Çin Tangshan eyaletinde yaşanan ve 240.000 kişinin ölümü ile sonuçlanan depremden 37 yıl sonra bir çalışma yapılmıştır.…”
Section: Dsm-5 Travma Sonrası Stres Bozukluğu Kontrol Listesi (Tssbkl)unclassified